Special Ones? The Effect of Head Coaches on Football Team Performance - Alex Bryson; Babatunde Buraimo; Alex Farnell; Rob Simmons (Institute of Labor Economics (IZA), 2021)
One expects those who lead organisations to affect their performance. If not why would organisations spend so much time and money appointing and incentivising their leaders? Yet there is little evidence establishing a causal link between leaders and organisational performance. Using game-by-game linked employer-employee data for professional football in four countries over fifteen seasons we compare the performance of teams after they have sacked their Head Coach with spells where the Head Coach remains in post. We undertake a similar exercise comparing performance after a Head Coach quits with that of teams where the Head Coach remains in post. We deal with the endogeneity of Coach departures using entropy balancing to reweight teams' performance prior to the departure of a Coach so that trends in team performance prior to the departure match spells which ended with a Coach remaining in post. Consistent with theory, Head Coach quits have little or no impact on team performance whereas teams who fire their Head Coach experience small but statistically significant improvements in team performance, although this positive impact is confined to circumstances in which a team holds onto the new Coach having sacked the previous Coach. Our results lend support to the proposition that teams can benefit from Head Coach turnover, firing them when it is optimal to do so, and replacing a Head Coach during the offseason.
Keywords: J63; Z22; 330; managerial performance; team performance; football; entropy balancing